Leptin (T3469C) and estrogen receptor (T1665G) gene polymorphisms and their associations to backfat thickness and reproductive traits of large white pigs (Sus scrofa L.) - Vega, Renato SA; Castillo, Ronne Matthews C.; Barrientos, Nyka Noelle B.; Llanes-Autriz, Mariedel M.; Byung-Wook Cho; de la Viña, Celia B.; Villa, Neilyn O. (2018)
The study was conducted to associate polymorphism of the leptin (LEP) and the estrogen receptor (ESR) genes with backfat thickness and reproductive performance in Large White sows. Nuclear DNA was isolated from hair follicles of 24 (for LEP) and 30 (for ESR) Large White sows in a commercial breeder farm. Amplification of the T3469C region of LEP and T1665G region of ESR was accomplished following digestion with Hinfl and PvuII restriction enzymes, respectively. Electrophoresis of the LEP digestion products revealed genotype frequencies of 0.625 for TT (n=15), 0.25 for TC (6), and 0.125 for CC (3).Meanwhile the ESR genotype frequencies for AA, AB, and BB were 0.50 (15), 0.37 (11), and 0.13 (4), respectively. LEP polymorphism was not related to backfat thickness at farrowing and 21 days of lactation. Significant genotype associations were observed only for total litter size at birth (p<0.05) and total litter size born alive (p<0.01). ESR polymorphism was not significantly different for backfat thickness, litter size at birth, litter size at weaning, weight at 21 days old, and weaning to estrus interval. The three Large White sows having the CC LEP genotype have14 litters size born alive. It is recommended that more Large White CC genotype sows be kept and monitored for further validation of the T3469C LEP polymorphism as candidate marker for sow productivity.
Includes bibliographical references (pages 299-300)
Keywords: Agriculture; Leptin; Reproductive traits; Single nucleotide polymorphism; Estrogen receptor; Large white pigs